2016
DOI: 10.18063/ijps.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Infant mortality differentials among the tribal and non-tribal populations of Central and Eastern India

Abstract: Higher infant mortality among tribal populations in India is well-documented. However, it is rare to compare factors associated with infant mortality in tribal populations with those in non-tribal populations. In the present paper, Cox proportional hazards models were employed to examine factors influencing infant mortality in tribal and non-tribal populations in the Central and Eastern Indian states using data from the District Level Household Survey-III in [2007][2008]. Characteristics of mothers, infants, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Similar to previous studies our results also show that female child had a higher risk of death during infancy than a male child in the poor-performing states in India 24–27. The reason of excess female infant mortality could be human intervention at different stages of life cycle.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies our results also show that female child had a higher risk of death during infancy than a male child in the poor-performing states in India 24–27. The reason of excess female infant mortality could be human intervention at different stages of life cycle.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies about infant mortality in India either took prevalence and determinants route 4,9,11 or explained survival estimates among infants 12,17 or studied mortality clustering among infants. 18,19 We could find very limited literature that examined the contribution of different factors in explaining the inequality in infant mortality in India.…”
Section: Discussionmentioning
confidence: 99%
“…We could not verify our findings with previous studies as this study primarily focused on examining the contribution of various factors to inequality in infant mortality. However, various studies have highlighted the importance of mother's education, 25 open defecation, 10 antenatal care, 26 urban place of residence, 17 colostrum feeding, 27 and use of hygienic cooking fuel 28 in reducing the infant mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that caste differences in infant and child mortality are substantially reduced when parental socioeconomic characteristics are held constant [21]. In a recent study by Ranjan et al (2016) [25], the authors concluded that the gap in infant mortality between tribal and non-tribal populations was substantial in the early months after birth, narrowed between the fourth and eighth months, and grew after that. The study by Dommaraju and colleagues (2008) [17] examined the association of caste on child mortality and maternal health care utilization in rural India.…”
Section: Introductionmentioning
confidence: 99%